Georgia Architectural and Historic Properties Survey of Moore's Grocery, 522 West St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Moore's Grocery, 522 West St., Valdosta, Ga., December 1980. One story shotgun which has been converted for commercial use. Tin gabled roof. Clapboard siding. Interior chimney. Exposed rafters. Fair condition. Date of Construction: Prior to 1922. Typical of the small neighborhood store found in older sections of town. Significant as part of a potential N.R. district along West St.
Georgia Architectural and Historic Properties Survey of Moore's Grocery, 522 West St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 80.5 MB (84,466,800 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)